Cardiorenal syndrome or renocardial syndrome:A review - Otukesh, Hasan; Mehralizadeh, Semira (Journal of Pediatric Nephrology, 2016)
Cardirenal syndrome,as a complex pathophysiological disorder of the heart and kidneys,whereby acute or chronic dysfunction in one organ may induce acute or chronic dysfunction in the other, has been under focus of interest for a long time.In this review we intend to define the interaction between the kidneys and the heart and different circulating components to characterize the pathophysiological course of the syndrome and discuss the new approaches for the management of this entity.